Betulin isolated from Pyrola incarnata Fisch. inhibited lipopolysaccharide (LPS)-induced neuroinflammation with the guidance of computer-aided drug design. Issue 12 (15th June 2020) - Liu, Qian; Liu, Jin-Ping; Mei, Jia-Hui; Li, Shuang-Jun; Shi, Li-Qiao; Lin, Zong-Hao; Xie, Bai-Yan; Sun, Wei-Guang; Wang, Zhen-Yu; Yang, Xi-Liang; Zou, Yu; Fang, Wei
Graphical abstract: Highlights: Ten compounds including betulin were isolated from P. incarnata and elucidated. Betulin suppressed LPS-induced activation by inhibiting inflammatory cytokines. Molecular docking suggested possible anti-inflammatory mechanism of betulin. Betulin reduced iNOS expression, prevented JNKs and phosphorylation of NF-κB/p65. Abstract: This study aims to investigate active phytochemicals isolated from Pyrola incarnata Fisch. ( P. incarnata ) and their protection against neuroinflammation induced by LPS. Betulin, accompanied with other 9 compounds, were isolated from P. incarnata and elucidated by spectroscopic analysis ( 1 H-, 13 C NMR). ELISA kits and the measurement of NO production based on Griess reaction showed that betulin (5 ) (250 μg/mL) could suppress LPS-induced activation of microglial cell BV-2 better than others by inhibiting inflammatory cytokines (TNF-α, IL-6, IL-1β) expression and NO production. With the guidance of computer-aided drug design and the analysis of biological experiment, we demonstrated betulin could reduce LPS-induced iNOS expression, prevent JNKs pathways, and down-regulate the phosphorylation levels of NF-κB/p65. In conclusion, betulin isolated from P. incarnata possessed outstanding anti-neuroinflammation potential, presumably related to iNOS expression, JNKs and NF-κB/p65 pathways. Therefore, Pyrola incarnata may be a valuable natural resource and betulin is a potential drug for the treatment of neurodegenerative disorders by inhibiting inflammatory mediators.